Sistem Informasi Manajemen Rantai Pasok Pariwisata Untuk Pembuatan Produk Wisata Pada Agen Tour dan Travel dengan Analisis Swot dan Metode Analytic Network Process ) - Kusumawardani, Dwi Mustika; Sediyono, Eko (JSINBIS (Jurnal Sistem Informasi Bisnis), 2016)
The development of services company in tourism is increasing. Therefore each tour & travel agent should be able to improve the quality of attractive and competitive products. This research builds a system analysis of supply chain management in the manufacturing of tour packages with SWOT analysis and Analytic Network Process (ANP). SWOT analysis is one way to decide marketing strategy for the company to able to face global competition. In this study, a SWOT analysis is used to select the best suppliers in tourism sector. Suppliers include: hotels, restaurants, attractions and accommodations. Combination of the best suppliers used as in one product of tour package. While the method of Analytic Network Process is used to rank the tour package has been obtained previously. In addition, this method is applied because it can provide information about the most influential of criteria in making tour package. This method conducted by looking at dependency relationship between among criteria. Then give them weight among criteria, sub-criteria and alternatives. The criteria used in the method of Analytic Network Process are: product, price, place and promotion. The results obtained from this research is the system analysis of supply chain management of tourism which capable of producing an attractive and competitive tour packages form of tour packages 1 with a value of 0.53. In addition, this information system provides information that the most influential criteria in making tour package is the product criteria with a value of 0.30. The next criterion which affects the making of attractive and competitive tour packages is price of criteria with a value of 0.28.